Volume 1B: General 1978
DOI: 10.1115/78-gt-126
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Combustion Turbine Burner Performance With Coal Derived Liquids Having High Fuel Bound Nitrogen

Abstract: The Electric Power Research Institute is conducting a program to develop combustion turbine burners for high-bound nitrogen, highly aromatic, low hydrogen/carbon ratio coal derived liquids. The problems of fueling standard units with these liquids are being determined, with special emphasis on environmental aspects. Small-scale and full-scale laboratory combustor tests are described. Results from earlier tests are surveyed, especially with regard to smoke production NOx emissions and flame radiation. A unique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1980
1980
1996
1996

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The parameter, "Smoke for CDL/Smoke for PDS," is used to make comparisons of the subscale smoke performance of the coal liquids and surrogates. Pillsbury, et.al., (3) showed that smoke data from different combustors in different laboratories could be correlated with respect to hydrogen content in this fashion. At three of the four combustor outlet temperatures studied --839, 1172 and 1311 K (1050, 1650 and 1900 F) --smoke values of the CDL and PDS fuels were normalized using the baseline data taken immediately preceding the test.…”
Section: Smoke Emissions With the Surrogate Fuelsmentioning
confidence: 88%
“…The parameter, "Smoke for CDL/Smoke for PDS," is used to make comparisons of the subscale smoke performance of the coal liquids and surrogates. Pillsbury, et.al., (3) showed that smoke data from different combustors in different laboratories could be correlated with respect to hydrogen content in this fashion. At three of the four combustor outlet temperatures studied --839, 1172 and 1311 K (1050, 1650 and 1900 F) --smoke values of the CDL and PDS fuels were normalized using the baseline data taken immediately preceding the test.…”
Section: Smoke Emissions With the Surrogate Fuelsmentioning
confidence: 88%
“…Gas turbines have the capability to burn a wide variety of fuels. Combustor and fuel injector design modifications have been able to accommodate fuels which have included: natural gas, blast furnace gas, coal gas, distillate fuel, residual fuel, crude oil, methanol, propane, coal derived liquids, and shale oil (Pillsbury et al, 1974(Pillsbury et al, , 1978(Pillsbury et al, and 1979Seglem and DeCorso, 1980). Burning fuels which have potentially corrosive elements requires that fuel contaminant specifications be set (Wenglarz and Menguturlc, 1981).…”
Section: Special Fuelsmentioning
confidence: 99%
“…Contributed by the Gas Turbine Division of The American Society of Mechanical Engineers for presentation at the Gas Turbine Conference & Products Show, New Orleans, La., March 10-13, 1980. Manuscript received at ASME Headquarters December 11,1979. Copies will be available until December 1, 1980.…”
Section: Introductionmentioning
confidence: 99%